Contemporary Russian cinema : symbols of a new era - Strukov, Vlad, 1973- (Edinburgh University Press, 2016)
Explores the symbolic mode in relation to contemporary Russian film. One of the first books to explore Russian cinema in the new millennium, this volume captures the emergence of a new cinematic sensibility and interprets it through the framework of the symbolic mode. Analysing films by established directors such as Sokurov, Zviagintsev and Zel'dovich, as well as lesser-known filmmakers like Balabanov, Fedorchenko and Kalatozishvili, Contemporary Russian Cinema: Symbols of a New Era explores the particular style of film presentation that has emerged in Russia since 2000, characterised by its use of highly abstract concepts and visual language. Whether directed towards a mystical world, or even towards an afterlife, the symbolic mode defines the emergence of a specific mindscape which has escaped previous representational forms and is intrinsically linked to Russia's dramatic political and economic development since the turn of the 21st century. Key Features. Offers a new perspective on contemporary film in the symbolic mode Provides a thorough examination of works by established directors such as Sokurov, Zviagintsev and Zel'dovich, as well as lesser-known filmmakers like Balabanov, Fedorchenko and Kalatozishvili